Good Faith in Successive Credit and Sharia Financing Restructuring: Comparative Regulatory Approaches in Indonesia and Japan - Marwah Marwah; Rifaatul Mardhahiswana; Aulia Rifai; Muhammad Aswan; Novytha Sary (Justicia Islamica, 2026)
This article examines how to assess the principle of good faith in restructurings, which may deviate if it neglects the debtor’s repayment capacity. This study employs a normative legal approach, using statutory, conceptual, and comparative analysis of Indonesia and Japan, based on four variables: debtor eligibility, supervisory model, business monitoring, and restructuring frequency limits. The analytical framework uses the principles of good faith and prudential banking as objective standards, supported by the theory of justice and legal certainty. The findings show that restructuring policies in Indonesia and Japan reflect distinct paradigms in interpreting good faith. Although the Indonesian Financial Services Authority limits restructuring to a maximum of three times, conventional banking tends to be flexible, allowing successive restructurings without adequate debtor eligibility. In contrast, Islamic banking imposes stricter limitations due to Sharia compliance. In contrast, Japan does not regulate a numerical limit, but the Japanese Financial Services Agency strictly monitors successive restructuring. This article proposes a model for objectively assessing good faith as a governance standard by integrating contract law, prudential banking principles, and Islamic ethics to ensure that restructuring supports debtor repayment capacity and financial system stability.